FAKTOR - FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN SERTA DAMPAKNYA TERHADAP AKUNTABILITAS ORGANISASI (Studi pada Universitas Brawijaya Malang) - Ipma Rahman Yudanto (Jurnal Ilmiah Mahasiswa FEB, 2015)
The aim of this study is to predict the influence of leadership style, compensation system suitability,  internal control effectiveness and  accounting  procedures adherence on  fraud tendency and its impact on organizational accountability in government agencies. This studyuses  a  convenience  sampling  method  in  primary  data  collection with  a  sample  of  160 respondents. Data analysis method used is multiple regression analysis. Results show that leadership   style,   compensation   system   suitability,   internal   control  effectiveness  and accounting  procedures  adherence  negatively  affect  fraud tendency  as  well  as  fraud propensity has a negative effect on organizational accountability. The results of this study indicate that the leadership style have a dominant influence in affecting the tendency of fraud. It shows that the type of a leader to lead can affect the performance of employees and it can be used by UB to suppress fraud tendencies. Other things which can be used to reduce fraud tendency are recognizing and appreciating employees, setting realistic goals for the institution, delivering a clear direction and desired objectives, inspiring subordinates and giving praise or rewards to employees who complete tasks on time.Keywords:  Fraud  tendency,  leadership  style,  compensation  system  suitability,  internal control   effectiveness,   accounting  procedures   adherence,   accountability,   Brawijaya University.